Optimizing Urban Water Systems: A Study of Leakage Scenarios in Continuous and Intermittent Distribution Systems - Kaywan Ahmed; Younes Aminpour (Advances in Civil Engineering and Environmental Science, 2024)
The primary component of an urban system is its water supply. In addition to wasting water, leakage has a significant economic impact. This study develops a leak detection system by comparing intermittent and continuous water systems to reduce leakage and enha nce monitoring. Various scenarios were examined, including no leaks (NL), a single leak (SL), and multiple leaks (ML), with intermittent water distribution (IWD) and continuous water distribution (CWD) systems operating at consistent flow rates ranging from 10 to 25 l/min. Initially, the pipeline of the intermittent water distribution system is not fully water-filled, but the discharge changes over time to achieve the desired flow rate. To realistically simulate these conditions in the lab, manual main valves were used to adjust the flow rate, targeting adjustments within 20 to 25 seconds. As a result, the continuous water distribution system exhibits higher leakage than the intermittent system. Specifically, opening the first valve in the loop system leads to greater losses compared to multiple leaks. The branched system suffers significant losses due to increased leakage points, whereas the CWD experiences higher leakage rates across all comparisons. Overall, across all system types, the CWD has a higher leakage rate than the IWD for the same flow rate.